Analysis of the predictive factors for critical illness of COVID-19 during treatment - Relationship between serum zinc level and critical illness of COVID-19 (2020)
Objectives: Because most severely ill patients with COVID-19 in our hospital showed zinc deficiency, we aimed to examine the relationship between the patient’s serum zinc level and severe cases of COVID-19. Methods: Serum zinc <70 µg/dL was defined as the criterion for hypozincemia, and patients continuously with serum zinc <70 µg/dL were classified in the hypozincemia cohort. To evaluate whether hypozincemia could be a predictive factor for critical illness of COVID-19, we performed the multivariate analysis by employing logistic regression analysis. Results: Prolonged hypozincemia was found to be a risk factor for a severe case of COVID-19. In evaluating the relationship between the serum zinc level and severity of patients with COVID-19 by multivariate logistic regression analysis, critical illness can be predicted through the sensitivity and false specificity of an ROC curve with an error rate of 10.3% and AUC of 94.2% by only two factors: serum zinc value (P=0.020) and LDH value (P=0.026). Conclusions: Proper management of the prediction results in this study can contribute to the establishment and maintenance of a safe medical system, taking the arrival of the second wave and spread of COVID Journal Pre-proof -19 in the future into consideration.